Atezolizumab plus bevacizumab in patients with unresectable or metastatic mucosal melanoma: 3‐year survival update and multi‐omics analysis - Jie Dai; Tianxiao Xu; Lifeng Li; Meiyu Fang; Jing Lin; Jun Cao; Xue Bai; Caili Li; Xiaoting Wei; Junjie Gu; Yaoyao Liu; Xuan Gao; et al. (Clinical and Translational Medicine, 2025)
Abstract Background Atezolizumab plus bevacizumab has shown promising efficacy in advanced mucosal melanoma in the multi‐centre phase II study. This report updates 3‐year survival outcomes and multi‐omics analysis to identify potential response biomarkers. Methods Forty‐three intention‐to‐treat (ITT) patients received intravenous administration of atezolizumab and bevacizumab every 3 weeks. Available samples underwent whole exome sequencing, transcriptome sequencing and targeted bisulphite sequencing to assess correlations with clinical outcomes. Results With a median follow‐up of 40.3 months, the median overall survival (mOS) was 23.7 months (95% confidence interval [CI], 15.1–34), and the 3‐year OS rate was 28.7% (95% CI, 17.6%–46.8%). Patients with upper site melanoma exhibited longer progression‐free survival (PFS), higher tumour neoantigen burden (TNB) and greater copy number variations (CNVs) burden compared to those with lower site melanoma. NRAS mutations were associated with enhanced angiogenesis, with five of six patients achieving partial response. Inflammatory cell infiltration, angiogenic status and activation of the SMAD2 and p38 MAPK pathways may be prognostic indicators. Conclusions This 3‐year updated analysis confirms the sustained efficacy of atezolizumab in combination of bevacizumab in patients with advanced mucosal melanoma. Inflammatory cell infiltration and angiogenic status were associated with therapeutic response. Furthermore, mucosal melanoma of upper site and NRAS mutation appear to be good predictors of response to immune checkpoint inhibitor and anti‐angiogenic combination treatment. Targeting SMAD2 and p38 MAPK pathways may further improve the outcome of mucosal melanoma. Key points 3‐year follow‐up study confirmed the therapeutic efficacy of atezolizumab combined with bevacizumab Tumors in the upper site and NRAS mutations are more sensitive to treatment Inflammatory cell infiltration, angiogenic status, and activation of the SMAD2 and p38 MAPK pathways may be prognostic indicators